Perspectives and Theories of Social Innovation for Ageing Population - Andrzej Klimczuk; Łukasz Tomczyk (Frontiers Media SA, 2020)
In recent years we may observe increasing interest in the development of social innovation both regarding theory as well as the practice of responding to social problems and challenges. One of the crucial challenges at the beginning of the 21st century is population ageing. Various new and innovative initiatives, programs, schemes, and projects to respond to negative consequences of this demographic process are emerging around the world. However, social theories related to ageing are still insufficiently combined with these new practices, social movements, organisational models, and institutions. Many scholars are still using notions and tools from classical theories of social gerontology or the sociology of ageing such as disengagement theory, activity theory, and successful and productive ageing. Such theories do not sufficiently explain ageing in the context of, for example, a broad use of the information and communications technologies (ICTs) including robotics and automation, new healthcare and long-term care models, advancements in the development and governance of age-friendly environments, and public engagement of older adults into co-production of services delivered by public, private, non-governmental as well as non-formal entities.
Keywords: J14; J18; O35; 330; ageing; aging; older adults; older people; social gerontology; sociology of aging; sociology of ageing; ICT; robotics; social innovation; care; caregivers; age-friendly; public health; long-term care; healthcare; governance; NGOs